Evidence map of diagnosis, treatment, prognosis, prevention, and control in visceral leishmaniasis - Andressa Barros Ibiapina; Francisca Miriane de Araújo Batista; Bruno Guedes Alcoforado Aguiar; Vagner José Mendonça; Dorcas Lamounier Costa; Carlos Henrique Nery Costa; Carmen Verônica Mendes Abdala (Pan American Health Organization, 2022)
Objective. To develop an evidence map on visceral leishmaniasis prevention, control, diagnosis, treatment, and prognosis. Methods. Systematic reviews on visceral leishmaniasis were searched using MEDLINE/PubMed and Virtual Health Library. After selection, each included systematic review was assessed, characterized, and categorized by intervention type and by outcomes, according to the methodology offered by the PAHO/WHO Latin American and Caribbean Center on Health Sciences Information (BIREME). The methodological quality was assessed using the AMSTAR2 tool to determine the confidence level of the evidence obtained. Results. Among the prevention and control interventions, insecticide spraying, bednets, dog collars, and dog culling were the most assessed, emphasizing that insecticidal dog collars can reduce visceral leishmaniasis incidence in dogs. Regarding diagnosis, polymerase chain reaction (PCR), rK39 immunochromatographic test (rK39 ICT), and direct agglutination test (DAT) presented high sensitivity and specificity. As for treatment, pentavalent antimonials and amphotericin B were the most analyzed drugs and showed therapeutic success; however, serious adverse events can occur due to their use. The prognostic factors identified were anemia, edema, bleeding, jaundice, age, and HIV coinfection. Conclusions. The evidence map developed shows rK39 ICT and DAT as promising diagnostic alternatives and reinforces the efficacy of liposomal amphotericin B and pentavalent antimonials. Insecticide-impregnated dog collars appear as a promising measure for the control of visceral leishmaniasis, but there is also a need for future studies and reviews with higher methodological quality, especially on prevention and control interventions.